2: Genetic- and Mobilization-Based Alterations in Matrix Alignment to Mitigate Aberrant Cell Fate Determination. (July 2021) - Pagani, Chase A.; Strong, Amy L.; Livingston, Nicholas; Sun, Yuxiao; Hespe, Geoffrey E.; Nunez, Johanna; Patel, Nicole; Huber, Amanda K.; Ge, Chunxi; Franceschi, Renny; Levi, Benjamin
Abstract : Purpose: Cells recognize mechanical cues from the extracellular environment through interactions with matrix proteins, such as collagen. Following injury, fibrotic deposition of collagen can lead to aberrant cell differentiation and failed healing. Aligned collagen matrices can drive PDGFRα+ mesenchymal progenitor cells (MPCs) towards osteochondral lineages, leading to heterotopic ossification (HO). Previous work has shown that reducing mechanical strain by immobilizing a limb prevents the formation of an aligned extracellular matrix (ECM), leading to altered MPC differentiation, however, the cellular mechanisms of matrix reorganization following injury remain unclear. Using novel bioinformatics approach, we identified discoidin domain receptor 2 (DDR2) as a key MPC specific tyrosine kinase receptor that interacts with the fibrillar collagen matrix. We hypothesized that DDR2 activation leads to regulation of ECM alignment and therefore serves as a novel upstream regulator of mechanotransductive signaling following musculoskeletal repair. Methods: Heterotopic ossification was induced using a proven mouse model of 30% total body surface area burn with concurrent Achilles' transection in Ddr2 deletion ( Ddr2 slie/slie ) and littermate control mice on the C57/BL6J background. In separate experiments, ankle joint immobilizers were placed on injured mice for 1, 2 or 3 weeks after burn/tenotomy. Tissue from Ddr2 deleted, immobilized and mobile control mice were harvested for immunofluorescence histology, second harmonic generation of collagen fiber histology at 1, 3 and 9 weeks after injury (SHG) (n=4/group). HO site tissue was also harvested prior to injury and at 1 and 6 weeks after burn/tenotomy and processed for Single-Cell RNA sequencing (scRNA seq) and single nucleus assay for transposase-accessible chromatin (snATAC) using 10X Sequencing and downstream analysis using Seurat 4.0.1 and Signac 3.1.5. Results: Single-cell RNA sequencing showed that genes for collagen type 1 and 3 and Ddr2 are highly upregulated in MPCs following injury. SnATAC showed increased open chromatin reads in the promoter of MPCs following injury (not shown). Utilizing SHG, we found that the collagen matrix is aligned at three-weeks following injury, but one week of limb immobilization was enough to prevent aligned collagen. The active phosphorylated form of DDR2 (pDDR2) was decreased in PDGFRα+ MPCs within immobilized samples, suggesting that DDR2 may affect matrix alignment. Ddr2 slie/slie had more disorganized collagen matrix nine weeks following injury and significantly reduced HO. Conclusions: This is the first work to alter collagen matrix organization by genetic modification and mobilization protocols and identifies DDR2 as a critical upstream receptor in matrix organization and aberrant progenitor differentiation following injury. DDR2 antagonism could have therapeutic potential in preventing heterotopic ossification following traumatic injury.